Recent Advances in Molecular Pharmacology of the Histamine Systems: Roles of C-terminal Tails of Histamine Receptors - Kuramasu Atsuo; Sukegawa Jun; Yanagisawa Teruyuki; Yanai Kazuhiko (Elsevier, 2006)
Abstract.: G-protein-coupled receptors (GPCR) represent a large and diverse superfamily of integral membrane proteins to which histamine receptors belong. Increasing numbers of proteins have been identified to interact with the C-termini of GPCRs. These interactions are implicated in targeting, trafficking, and fine-tuning of signaling of GPCRs. Although the C-terminus of the histamine H2 receptor has been suggested to play in agonist-induced internalization of the receptor, roles of the C-termini of the other three histamine receptors are not known. To date, there is no protein identified to interact with the C-termini of histamine receptors. Keywords:: G-protein-coupled receptor, histamine receptor, C-terminus, internalization